Evaluation of early maturing cowpea (Vigna unguiculata) germplasm for variation in phosphorus use efficiency and biological nitrogen fixation potential with indigenous rhizobial populations - Abaidoo, Robert C.; Dare, M.O.; Killani, S.; Opoku, A. (Cambridge University Press, 2017)
Cowpea genotypes that efficiently utilize phosphorus (P) with high potential for biological nitrogen (N) fixation (BNF) are vital to sustainable cropping systems in West Africa. A total of 175 early maturing cowpea genotypes were evaluated in 2010 and 2011 for P use efficiency (PUE) and BNF with an indigenous rhizobial population at Shika in the Northern Guinea savanna of Nigeria. There were significant genotypic variations for all 11 variables measured. The P utilization index, percentage N derived from the atmosphere and total N fixed ranged between 2·10–4·67, 31·3–61·86% and 11·86–50 kg/ha, respectively. The 175 early maturing cowpea genotypes were divided into five categories using principal component analysis (PCA), whereby total N fixed was associated with N and P uptake and plant biomass yield. Complete linkage cluster analysis revealed a total of three distinctive clusters having remarkable correspondence with the PCA. Some genotypes were identified as potential candidates for further breeding programmes using high PUE genotypes with relatively high capacity for BNF and indigenous rhizobial populations.